Comportamento alimentar e social de bezerras leiteiras F1 Holandês x Gir durante a fase de aleitamento e desaleitamento - Juliana Campos Carneiro (2015)
ABSTRACT - This studys goal is to evaluate the behavior of F1 Holstein x Gir dairy calves raised in individual pens, inside a brickwork shed from milk feeding to weaning. 36 F1 Holstein x Gir dairy calves were used. After birth they were weighed, identified, separated from their mothers and housed in sand-covered pens with troughs for total mixed ration and water ad libitum. They received 10% of their body weight in colostrum which had immunoglobulin concentration higher than 50g/L. Up to their third day of life the dairy calves were given 6 liters of transition milk, divided between two feedings per day. From the fourth day on the animals received the following experimental diet: six liters of milk a day divided between two feedings; water, and total mixed ration (95% concentrate; 5% Tifton 85 hay) ad libitum. Ruminal pH, -hidroxibutirate in serum, and diet consumption were measured. The means were calculated weekly. Rectal temperatures were checked in the morning and in the afternoon every other day. Abrupt weaning was executed on day 80. Frequency and duration (Scan) of the animals behavior in the first weeks of life were evaluated as random blocks, in which the animals were the blocks. For the weaning behavior Scan, randomized Split-Plot block design was used. According to BGHI (Black Globe-humidity index) values for the months of October, November, and December, the animals were in thermal comfort. However, during the months of January, February, March and April, the animals were under stress. The mean values for rectal temperature were within the normal limits (38.0 to 39.3 ºC). Dairy calves ingestive behavior differed (p<0.05) between weeks during the milk feeding stage. The dairy calves spent more time lying down in the first (72.3%) and second (67.8%) weeks compared to the following weeks. The average dry matter intake of concentrate was different between weeks (p<0.05), which indicates effect of age. The abrupt weaning executed in this study did not compromise food consumption. Ruminal pH values were higher (p<0.05) at 14 and 28 days than at 42 and 56 days. -hidroxibutirate concentration in serum increased with age (p<0.05). The nature of the housing used during the milk feeding stage allowed for visual contact amongst the dairy calves, which may have been responsible for the great number of activities during the socialization stage. In the present studys circumstances, within thermal comfort limits, the F1 Holstein x Gir dairy calves adapted to the individual pen rearing system. In the weaning stage, the dairy calves did not present any signs of stress during evaluation.